An ethnographic study of the spiritual dimension of a Church of England primary school - Lumb, Anne (2014)
The research documented in this thesis took place against a background of concern for the wellbeing of children, the educational standards being achieved in schools and questions about the purpose of education itself, particularly within a Christian framework. The focus of the research was an ethnographic study into the factors influencing the development and nurture of children’s spirituality in a Church of England Primary School where faith, belief and spirituality are explored as part of the educational experience of pupils. All schools are expected to provide opportunities for children’s spiritual development according to the 1944 Education Act, which replaced the term “religion” with the term “spiritual”. For Anglican Church Schools such provision is perceived to be a priority. However, because they are church schools within a state system they are subject to the differing expectations of a dual inspection system. This creates certain tensions and a degree of complexity for the schools. Beginning with a focus on the potential contribution that Philosophy for Children could make to children’s spirituality, the study broadened its scope to take account of the larger questions and concerns (outlined above) which were impacting on the potential for schools to offer opportunities for spiritual development to children during their primary school experience. The case study is analysed using Bernstein’s pedagogic theories and models to elucidate the “double tension” which exists for Anglican Church Schools as they seek to achieve high academic standards and provide opportunities to explore spirituality both of which are central to the mission of church schools. This tension was evidenced in the leadership style, language and pedagogy operating within the case study school. The study concludes that recognising this tension seems to be a prerequisite for supporting church schools as they seek to fulfil their mission within the current educational climate.